Impact Of Active Learning Strategies Cooperation And Peer Mentoring On Students’ Football Dribbling And Passing Skills - Sabaa Muhamad Hameed; Mohammed Abd Ulhussien; Sajad Aiad Hadi (Musamus Journal of Physical Education and Sport (MJPES), 2026)
The study aimed to identify effect of two active learning methods cooperative learning and peer mentoring on developing dribbling and passing skills in football among first-year students at College of Physical Education and Sports Sciences, Wasit University, for academic year 2024–2025, and to conduct a comparison between two methods to determine which is better. researcher used experimental method with an equivalent groups design. research sample consisted of (30) students, who were randomly distributed into three groups two experimental groups and one control group, with (10) students in each group. experiment was conducted at college sports field during period from 1/10/2025 to 1/2/2026, and equivalence and homogeneity were ensured for variables of height, weight, and prior skill performance. Key findings active learning groups (cooperative and peer-guided) achieved a significant advantage in post-tests of dribbling and passing skills compared to control group that followed traditional method, results showed that "cooperative learning method" was superior to "peer mentoring method" in improving level of skill performance in football. Interactive strategies contributed to enhancing students’ motor coordination, teamwork, and self- confidence. study recommends adopting cooperative learning as a fundamental pillar in football skills training programs, and urges instructors to integrate active learning methods into their curricula to improve quality of educational outcomes and increase students’ motivation towards motor learning.